2009
DOI: 10.1080/13607860902774436
|View full text |Cite
|
Sign up to set email alerts
|

Living with dementia: A systematic review of the influence of relationship factors

Abstract: A neglect of direct evidence from the person with dementia is identified, and possible ways of combating this are considered. Clinical implications are drawn with regard to supporting the carer, the person with dementia, and their relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
184
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(200 citation statements)
references
References 58 publications
9
184
0
7
Order By: Relevance
“…Working through the difficulties is a collaborative effort during which family members commit to the mutual relationship in spite of the disorder [33] . Our findings corroborate earlier findings that although memory disorders may adversely affect family relationships [9] , difficulties may also strengthen them and increase closeness between family members. Meaningful social support, especially from close relatives, was an important mainstay for the families, and promoted feelings of contentment with life.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Working through the difficulties is a collaborative effort during which family members commit to the mutual relationship in spite of the disorder [33] . Our findings corroborate earlier findings that although memory disorders may adversely affect family relationships [9] , difficulties may also strengthen them and increase closeness between family members. Meaningful social support, especially from close relatives, was an important mainstay for the families, and promoted feelings of contentment with life.…”
Section: Discussionsupporting
confidence: 82%
“…Previous research has shown that good quality of daily relationships and positive reciprocal communication can promote FCs' wellbeing [31,45,46] and support the positive adjustment of PMDs. It has also been found that enhanced relationship quality can maintain better emotional wellbeing of both the PMD and the FC, which can lead to more positive experiences of living with a memory disorder [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family/friends/carers who assume control, aiming to be supportive, may actually be tapping into the person's greatest fears of dependency (Frazier et al 2003). Maintaining involvement in everyday life is important for the dyad (Ablitt et al 2009). In our conceptualisation of self-management intervention for dementia, the aim is for this relationship to be positively supportive, but not to return all decisions to the person with early dementia as this may be neither feasible nor beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions addressing personal relationships for people living with dementia are scarce (Ablitt et al 2009). An intervention for people with dementia and their caregivers used joint-problem solving together and communication tasks, reporting better interaction in the intervention group and caregivers were more satisfied with the interaction, although the person with dementia's satisfaction was not reported (Corbeil et al 1999).…”
Section: Introductionmentioning
confidence: 99%